On prices in Myrdal's Monetary Theory (2006)
ABSTRACT: The aim of this paper is to show how Myrdal monetary theory can contribute to the study of the behaviour of prices in disequilibrium. The analysis explains the existence of a cumulative process based on the capacity of the entrepreneur to anticipate price variations. The variation in prices explains the persistence of the cumulative process. This, we argue, represents an opposite view of the one contained in Wicksell’s theory. Myrdal’s theory leads to the rejection of the quantity theory of money based on Wicksell’s approach. This comes as a surprising result knowing Wicksell believed his results confirmed this theory.